Extraction, detection, bioactivity, and product development of luteolin: A review - Fajian Ren; Ying Li; Hanyuan Luo; Song Gao; Shanshan Jiang; Jian Yang; Chaolong Rao; Yan Chen; Cheng Peng (Heliyon)
Luteolin is a kind of natural flavonoid, widely existing in a variety of plants, has been revealed to have a wide range of biological activities. In recent years, the research results of luteolin are abundant. Here we review the latest research results of luteolin in order to provide new ideas for further research and development of luteolin. In this paper, the focus of the search was published between 2010 and 2024 on the extraction and determination of luteolin, biological activities, and the development and application of luteolin products. A comprehensive search using the keyword ''luteolin'' was conducted in the PubMed, Web of Science and WIPO databases. Through the collection of related literature, this paper summarized a variety of extraction techniques of luteolin, including immersion extraction, solvent extraction, ultrasonic-assisted extraction, supercritical fluid extraction and so on. The determination methods include: thin layer chromatography (TLC), high performance liquid chromatography (HPLC), capillary electrophoresis (CE), electrochemical method (ED) and so on. In addition, the biological activities of luteolin, including antioxidant, anti-inflammatory, anti-tumor, antibacterial, analgesic and so on, were described. And luteolin as the main component of the product is being gradually developed, and has been used in the field of food, medicine and cosmetics. This paper provides a reference for further study of luteolin.